Familiarisation and reliability of the isometric mid-thigh pull in elite youth soccer players - Musham, C.; Fitzpatrick, J. F. (Sport Performance & Science Reports, 2020)
To identify if a `true` change in a measure of physical performance has occurred due to a specific stimulus, such as a training programme, an understanding of the minimum detectable change of that measure is required (1). When working with a new group of players, a confounding factor that may affect measurement error is the players` familiarisation withthe assessment. Documenting the number of assessments it takes to reach an acceptable level of reliability, and therefore the point at which players are said to be `familiar` with the assessment is a key piece of information that is rarely documented within the literature. With specific regard to the isometric mid-thigh pull (IMTP) there is no consensus within the literature on an optimal number of familiarisation sessions required (2) and therefore warrants further investigation.